2020
DOI: 10.3390/antib9020016
|View full text |Cite
|
Sign up to set email alerts
|

A Purification Strategy Utilizing Hydrophobic Interaction Chromatography to Obtain Homogeneous Species from a Site-Specific Antibody Drug Conjugate Produced by AJICAP™ First Generation

Abstract: In recent years, site-specific antibody drug conjugates (ADC)s have been in great demand because they have an expanded therapeutic index compared with conventional ADCs. AJICAP™ technology is a chemical conjugation platform to obtain site-specific ADCs through the use of a class of Fc-affinity compounds. Promising results from early technology development studies led to further investigation of AJICAP™ ADC materials to obtain site-specific and homogeneous drug antibody ratio (DAR) ADCs. Here we report site-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
0
27
1
Order By: Relevance
“…Furthermore, RP-HPLC analysis of all three ADCs after 144 days showed no decrease in DAR. These results indicate that the cysteine-based ADCs have sufficient stability for use in further studies and additional evaluations are ongoing in our research group [26][27][28][29][30][31][32][33] .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, RP-HPLC analysis of all three ADCs after 144 days showed no decrease in DAR. These results indicate that the cysteine-based ADCs have sufficient stability for use in further studies and additional evaluations are ongoing in our research group [26][27][28][29][30][31][32][33] .…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, a moderate-scale (one-hundred milligram) synthesis successfully demonstrated the scalability and reproducibility of the reduction conditions. Rather than purifying the hundred milligram scale ADCs by TFF or a related method, we applied larger, scaled-up gel filtration columns bridging the technology gap between research and process development stages [29][30][31][32][33] . Furthermore, a multi-month stability assessment of the resulting ADCs was conducted revealing changes in aggregation during 4 deg C storage.…”
Section: Resultsmentioning
confidence: 99%
“…Given the highly hydrophobic nature of payload molecules commonly used for ADC indications (e.g., PBD dimers, MMAE, etc. ), polishing of protein-based impurities like non-target DAR species often employ preparative HIC chromatography resin media for purifications [ 9 ]. Phenyl Sepharose High Performance (GE Healthcare) serves as a widely used stationary phase in the field given its small bead size (~34 µm diameter) and high ligand density.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to free-drug removal, if aggregates or undesired DAR variants are generated during the conjugation process, chromatographic purification steps are often required. Resin-based conventional chromatography such as hydrophobic interaction (HIC), cation exchange (CEX), and mixed-mode ceramic hydroxyapatite (CHT) have been used in aggregate removal or DAR polishing [ 7 , 8 , 9 ]. However, developing a preparative resin-based chromatography method can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of this approach as well as optimisation of the preparation and analysis of AJICAPt ADCs have subsequently been described. [240][241][242][243][244] Gupta et al reported the novel type of non-covalent ADCs that self-assemble via interaction of the antibody with a small molecule affinity ligand (Fig. 15F).…”
Section: C-/n-terminal Modificationsmentioning
confidence: 99%